The use of games in teaching English grammar to the 10th form students at Thang long high school - Tran, Thi Thanh Loan (2020)
This is the study on the use of games in teaching English grammar. The target population is the 10th form students at Thang Long high school. The main aims of this study are to discover the current situation of exploiting games in grammar lessons of the 10th form students, and to examine the feasibility of this teaching aid in a formal setting. To achieve these objectives, the researcher uses (1) questionnaires for the students, (2) interview for English teachers, and (3) an achievement test after six weeks of experiment. The results of the questionnaires show that the students learn grammar not only to pass their exams but to use it for communicative purposes as well. Additionally, the interview’s result indicates that teachers rarely included games in grammar lessons because of a number of reasons regarding students, teachers and the educational system. The researcher also finds it effective to apply games in grammar teaching due to the positive results of the achievement test. Acknowledging the obstacles and the students’ positive attitudes towards the use of games, it is recommended that games be used and adapted in the lesson plans to meet the individuals’ needs and abilities.